Generalized non-abelian Toda models of dyonic type - Gomes, J. F.; Sotkov, G. M.; Zimerman, A. H. (Iop Publishing Ltd, 2003)
The construction of a class of non-abelian Toda models admiting dyonic type soliton solutions is reviewed.